2019
DOI: 10.1021/acsomega.9b02050
|View full text |Cite
|
Sign up to set email alerts
|

Simulation on the Factors Affecting the Crystallization Process of FeNi Alloy by Molecular Dynamics

Abstract: This paper investigates the crystallization process of FeNi alloys with different impurity concentrations of Ni(x) [x = 10% (Fe90Ni10), 20% (Fe80Ni20), 30% (Fe70Ni30), 40% (Fe60Ni40), and 50% (Fe50Ni50)] at temperature (T) = 300 K and Fe70Ni30 at heating rates of 4 × 1012, 4 × 1013, and 4 × 1014 K/s at different temperatures, T = 300, 400, 500, 600, 700, 900, 1100, and 1300 K. Molecular dynamics models with the Sutton–Chen embedded interaction potential and recirculating boundary conditions are used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
4
14
0
Order By: Relevance
“…The given result shows that increasing N leads to l increase, and satisfy the formula: l = 18.021 − 138.153N −1/3 , corresponding to l~N −1/3 (Figure 5a) and −E tot proportional to N (Figure 5b). The results are consistent with the results of crystallizing process temperature (T m ) proportional with N −1/3 [74,75] and size (l or D) proportional with N −1/3 [67][68][69][70][71][72][73]. This proves that increasing atom number leads to crystalline atoms number FCC, HCP increase, Amor decrease, size increase, the total energy of system decrease; and the relationship with l~N −1/3 is an important result for future experimental implementation.…”
Section: Influence Of Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…The given result shows that increasing N leads to l increase, and satisfy the formula: l = 18.021 − 138.153N −1/3 , corresponding to l~N −1/3 (Figure 5a) and −E tot proportional to N (Figure 5b). The results are consistent with the results of crystallizing process temperature (T m ) proportional with N −1/3 [74,75] and size (l or D) proportional with N −1/3 [67][68][69][70][71][72][73]. This proves that increasing atom number leads to crystalline atoms number FCC, HCP increase, Amor decrease, size increase, the total energy of system decrease; and the relationship with l~N −1/3 is an important result for future experimental implementation.…”
Section: Influence Of Temperaturesupporting
confidence: 91%
“…Berendsen et al [65] have identified the transition temperature (T m ) of NiAu ranges from T m = 1100 K to T m = 1300 K with Au impurity concentration of 58% [66]. Combined with our recent results as Al [67], FeNi [68], AlNi [69], Ni 1−x Fe x [70], Ni 1−x Cu x [71], Ni [72,73], these results show that the transition temperature (T m ) of Ni material; T m is always proportional with atom number (N), N −1/3 [74,75], and the electronic structure of AuCu [76] and AgAu [77]. The phase transition of Ni material can be determined by stress or temperature [78][79][80][81], and the bonding length of Ni-Ni determined by the experimental method is r = 2.43 Å [82], while the simulation method of Dung, N.T is r = 2.45 Å [73], and P.H.…”
Section: Introductionsupporting
confidence: 81%
“… 18 Besides, in recent years, we have also studied the effects of heating rate, doping concentration, atom number, temperature of the structure, electronic structure, phase transition, and crystallization of alloys AuCu, 2 2 AlNi, 19 NiCu, 20 , 21 and FeNi. 22 23 The results obtained show that when the heating rate increases, the alloy changes from liquid state to amorphous state and vice versa, and that when the atom number increases, size increases and the energy of the system decreases. Increase (or decrease) of temperature leads to phase transition, from which the phase-transition temperature ( T m ), glass-transition temperature ( T g ), and density of the dictionary state changes have been determined.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, several researchers have used the Density Function Theory (DFT) method to study the structure, electronic structural properties, and transition temperature of conjugated polythiophene derivatives of optical active conjugate polymers [ 43–47 ]. Besides that, we have successfully studied the effects of temperature, pressure, atoms number, annealing time on the structure of Al metal [ 48 , 49 ], alloys AlNi [ 50 ], NiCu [ 51 ], FeNi [ 52 ], NiAu [ 53 ], polyethylene [ 54 ], electronic structure of AuCu [ 55 ] and polymers by using DFT method to control band gap by replacing doped -S atoms with -Se atoms [ 56 ] or replacing -H atoms with -CH 3 , -NH 2 , -NO 2 and -Cl [ 49 , 57–61 ] and 4 H-xiclopenta [2,1-b,3; 4-b′] or replacing dithiophene S-oxide with derivatives -O, -S, S = O, -BH 2 , -SiH 2 [ 47 , 62–64 ]. Recently, we have used the DFT method to study the effects of doped groups on the electrical structure and phase transition temperature of monothiophene C 13 H 8 OS-X (X = -H, -OH, -Br, -OC 2 H 5 , -OCH 3 ).…”
Section: Introductionmentioning
confidence: 99%